Practice patterns among early-career primary care (ECPC) physicians and workforce planning implications: protocol for a mixed methods study - Richard J Gibson; Tara Sampalli; Tara Kiran; Richard H Glazier; Agnes Grudniewicz; Kimberlyn McGrail; David Snadden; Ian Scott; M Ruth Lavergne; Laurie J Goldsmith; David Rudoler; Emily Gard Marshall; et al. (BMJ Open)
Introduction Canadians report persistent problems accessing primary care despite an increasing per-capita supply of primary care physicians (PCPs). There is speculation that PCPs, especially those early in their careers, may now be working less and/or choosing to practice in focused clinical areas rather than comprehensive family medicine, but little evidence to support or refute this. The goal of this study is to inform primary care planning by: (1) identifying values and preferences shaping the practice intentions and choices of family medicine residents and early career PCPs, (2) comparing practice patterns of early-career and established PCPs to determine if changes over time reflect cohort effects (attributes unique to the most recent cohort of PCPs) or period effects (changes over time across all PCPs) and (3) integrating findings to understand the dynamics among practice intentions, practice choices and practice patterns and to identify policy implications.Methods and analysis We plan a mixed-methods study in the Canadian provinces of British Columbia, Ontario and Nova Scotia. We will conduct semi-structured in-depth interviews with family medicine residents and early-career PCPs and analyse survey data collected by the College of Family Physicians of Canada. We will also analyse linked administrative health data within each province. Mixed methods integration both within the study and as an end-of-study step will inform how practice intentions, choices and patterns are interrelated and inform policy recommendations.Ethics and dissemination This study was approved by the Simon Fraser University Research Ethics Board with harmonised approval from partner institutions. This study will produce a framework to understand practice choices, new measures for comparing practice patterns across jurisdictions and information necessary for planners to ensure adequate provider supply and patient access to primary care.